Analysis of the Effect of Neuro-Developmental Treatment (NDT) on Gross Motor Function in Children with Spastic Diplegic Cerebral Palsy: A Systematic Review - Izdihar, Haunan Naja; Pratama, Aditya Denny (UI Scholars Hub, 2026)
Effectiveness of Neurodevelopmental Treatment (NDT) in Children with Spastic Diplegia Cerebral Palsy: A Systematic Review Background: Neurodevelopmental Treatment (NDT) is commonly used in pediatric rehabilitation to improve motor function in children with cerebral palsy, particularly those with spastic diplegia. Methods: This systematic review followed PRISMA 2020 guidelines. Seven studies published between 2018 and 2024 were identified through electronic databases, including PubMed, Scopus, ProQuest, ScienceDirect, SpringerLink, Cochrane Library, Google Scholar, and Crossref. Results: The included studies reported improvements in gross motor function, posture, balance, and daily functional independence following NDT, particularly when combined with other therapeutic interventions. However, outcome measures and intervention protocols varied across studies. Conclusion: Neurodevelopmental Treatment may provide potential benefits for improving gross motor function and functional abilities in children with spastic diplegic cerebral palsy, although the certainty of evidence remains limited.